Comorbidities and Factors Determining Medical Expenses and Length of Stay for Admitted COVID-19 Patients in Korea - Jang SY; Seon JY; Yoon SJ; Park SY; Lee SH; Oh IH (Dove Medical Press, 2021)
Su Yeon Jang,1,* Jeong-Yeon Seon,1,* Seok-Jun Yoon,2 So-Youn Park,3 Seung Heon Lee,4,* In-Hwan Oh1,* 1Department of Preventive Medicine, School of Medicine, Kyung Hee University, Seoul, South Korea; 2Department of Preventive Medicine, Korea University College of Medicine, Seoul, South Korea; 3Department of Medical Education and Humanities, School of Medicine, Kyung Hee University, Seoul, South Korea; 4Division of Pulmonary, Sleep, and Critical Care Medicine, Department of Internal Medicine, Korea University Ansan Hospital, Ansan, South Korea*These authors contributed equally to this workCorrespondence: In-Hwan OhDepartment of Preventive Medicine, School of Medicine, Kyung Hee University, 26 Kyungheedae-ro, Dongdaemun-gu, Seoul, 02447, South KoreaEmail parenchyme@gmail.comSeung Heon LeeDivision of Pulmonary, Sleep, and Critical Care Medicine, Department of Internal Medicine, Korea University Ansan Hospital, 123 Jeokgeum-ro, Danwon-gu, Ansan, Gyeonggi-do, 15355, South KoreaEmail lee-sh@korea.ac.krPurpose: No previous investigations of coronavirus disease 2019 (COVID-19) have estimated medical expenses, length of stay, or factors influencing them using administrative datasets. This study aims to fill this research gap for the Republic of Korea, which has over 10,000 confirmed COVID-19 cases.Patients and Methods: Using the nationwide health insurance claims data of 7590 confirmed COVID-19 patients, we estimated average medical expenses and inpatient days per patient, and performed multivariate negative binomial, and gamma regressions to determine influencing factors for higher outcomes.Results: According to the results, COVID-19 patients with history of ICU admission, chest CT imaging, lopinavir/ritonavir and hydroxychloroquine use stayed longer in the hospital and spent more on medical expenses, and anti-hypertensive drugs were insignificantly associated with the outcomes. Female patients stayed longer in the hospital in the over 65 age group but spent less in medical expenses that the 20– 39 group. In the 40– 69 age group, patients with health insurance stayed longer in the hospital and spent more on medical expenses than those aged over 65 years. Comorbidities did not affect outcomes in most age groups.Conclusion: In summary, contrary to popular beliefs, medical expenses and length of hospitalization were mostly influenced by age, and not by comorbidities, anti-viral, or anti-hypertensive drugs. Thus, responses should focus on infection prevention and control rather than clinical countermeasures.Keywords: medical costs, length of stay in hospital, comorbidities, COVID-19, Republic of Korea